Budgeting and allocation of feed resources - Leeuw, P.N. de; Dzowela, B.H.; Nyambaka, R. (International Livestock Centre for Africa, 1990)
Presents procedures for feed budgeting and allocation developed to access the quantity and quality of all feed components and to determine the production goals of each enterprise and allocates feed in relation to their requirements within the framework of overall feed supplies. Examines land, crops and feed resources of a model crude protein content and digestibility of rangeland, planted grass and legume forage, crude protein content and digestibility of crop residues, livestock holdings and daily feed requirement, monthly and annual feed requirements of different stock classes and diet composition of three livestock enterprises over three monthly periods.